IMPLIKASI TEORI BELAJAR SOSIAL (SOCIAL LEARNING THEORY) DARI ALBERT BANDURA DALAM BIMBINGAN DAN KONSELING - Tarsono Tarsono (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2010)
One of many ways of conceiving individual personality is by observing and analyzing his or her behavior. Bandura said that we need to know how people interact with the world around them. Sometimes any actions and his or her interaction with environment can be contrary to values that holds by their society. However—Bandura was also point out and human behavior can be predicted and modified by altering their behavior through learning. This learning processes must also considering the capacity of each person according to each own ability to think and how they interact with their surrounding environment. Based on social learning theory, behavior can be altered and modified through modeling, which is used to shape and molding a new behavior that can be approved by society and eliminating any unwanted behavior. Basic principle from this modeling is a goal that client can create, shape and mold new behavior through imitation or copying someone else’s behavior or people that become a model figure for them.